SOCIAL ADMISSION OF FRIENDS IS REVIEWED FROM SELF-CONFIDENCE AND SELF-DISCLOSURE - Mendonsa, Aris Cosmeardy; Mudjijanti, Fransisca (Educatio Vitae, 2019)
This study aimed to analyze the influence of the attitude of self-confidence and self-disclosure to peer social acceptance. The population of the sample was 109 students of SMPN 7 Madiun class VIII in 2017/2018. The author applied cluster sampling to obtain the sample. The data were obtained using questionnaire on peer social acceptance, self-confidence, self-confidence, and self-diclosure scale. The author prposed 3 (three) hypotheses: 1) self-confidence affected on peer social acceptence, 2) Self-disclosure affected on peer social accepyance, 3) self-disclosure and Self-disclosure affected on peer social acceptence. The data were analyzed by multiple linear regression technique. The result was equation of regression line Y = 55.170 + 0.355 + 0.177. The result of subsequent hypotheses were 1) self-confidence really affected on peer social acceptence and it was proven in t hit = 4,092> t table = 1,982, 2) self-disclosure did not affect in peer social acceptance and it was proven in t hit = 1,387 < t table = 1,982, 3) self-confidence and self-disclosure really affected peer social acceptance and it was proven in F hit = 27,043> F table = 3.080. Based on the results above, it can be conclouded: 1) the first minor hypothesis was accepted. 2) the second minor hypothesis was rejected 3) the major hypothesis was accepted.   Keywords: Peer Social Acceptance, Self-Confidence, Self-Disclosure